Análise temporal da dinâmica populacional de Aedes aegypti - Campos, Melina Aulino da Silva Machado de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Dengue virus is a major public health problem worldwide. Aedes (Stegomyia) aegypti is the main dengue vector. Since there is no specific treatment or effective vaccine, control measure is focused on vector control. It is believed that population density is higher in the warmer/rainy season than in cold/dry. The study aimed to genetically characterize population dynamics of Ae. aegypti during climatic variations. Collections were performed at least once in both periods over five years by oviposition traps at Botucatu city. The technique of TaqMan allelic discrimination was used for genetic analysis, in which SNPs from nine genes distributed on three chromosomes of the mosquito were genotyped. Bayesian analysis did not show variance on population structure over the five year period. The percentage of variation among samples in statistical analysis was low (Fst = 0.0028, p = 0.7634), furthermore the allele frequencies were constant. The results show that despite wide variation in the density of adults, population size does not vary. Therefore, there is variation in the prevalence of the species life stages: adults in warmer/rainy, and possibly eggs in cold/dry, resulting in different control strategies for each period. Moreover, estimation of population size should not consider only winged adults, but all other found life stages forms

A dengue é um dos principais problemas de saúde pública no mundo. Como não há tratamento específico ou vacina eficiente, a medida de controle é o combate ao vetor, sendo o culicídeo Aedes aegypti o principal. Acredita-se que a densidade populacional desse vetor é maior nos períodos quentes e chuvosos do ano, do que nos períodos frios e secos. O estudo analisou geneticamente a dinâmica populacional da espécie, mediante as variações climáticas. Foram feitas coletas pelo menos uma vez em ambos os períodos ao longo de cinco anos, por armadilhas de oviposição na cidade de Botucatu. A análise genética foi viabilizada pela técnica TaqMan de discriminação alélica, utilizando SNPs de nove genes distribuídos nos três cromossomos do mosquito. Pela análise bayesiana, não houve variação na estruturação populacional das coletas, e a análise estatística apresentou percentagem de variação entre as coletas foi baixa (FST = 0,0028; p=0,763), além disso as freqüências alélicas foram constantes. Os resultados mostram que, apesar da grande variação na densidade dos adultos, o tamanho populacional não varia. Portanto, há uma variação na prevalência da forma de vida da espécie: adultos nos meses quentes e chuvosos e, possivelmente ovos nos frios e secos; implicando em estratégias de controle diferentes para cada período. Além disso, a estimativa do tamanho populacional não deve considerar somente adultos alados, mas todas as outras formas de vida do mosquito encontradas
Keywords: Genética; Dengue; Aedes aegypti; Mosquito - Controle; Saúde pública